Common Gene Rearrangements in Prostate Cancer - Rubin, Mark A. (J Clin Oncol, 2011)
Prostate cancer is a common heterogeneous disease, and most patients diagnosed in the post prostate-specific antigen (PSA) era present with clinically localized disease, the majority of which do well regardless of treatment regimen undertaken. Overall, those with advanced prostate cancer at time of diagnosis do poorly after androgen withdrawal therapy. Understanding the biologic underpinning of prostate cancer is necessary to best determine the risk of disease progression and would be advantageous for the development of novel therapeutic approaches to impede or prevent disease. This review focuses on the recently identified common ETS and non-ETS gene rearrangements in prostate cancer. Although multiple molecular alterations have been detected in prostate cancer, a detailed understanding of gene fusion prostate cancer should help explain the clinical and biologic diversity, providing a rationale for a molecular subclassification of the disease.